Shifting the Paradigm in Community Mental Health : Toward Empowerment and Community - Nelson, Geoffrey B. (Geoffrey Brian); Ochocka, Joanna; Lord, John, 1943- (Book collections on Project MUSE., 2001)
"This study examines changes in the values and practices within community mental health that occurred between 1984 and 1998 in the Kitchener-Waterloo area. During this period, a distinct shift in policy coincided with a new emphasis on mental health reform. This unique two-and-a-half year study examined one community in depth by looking at the changes that occurred and their effects on individuals, organizations, and policy." "Throughout the course of the study, most of the changes in policy and practice focused on stakeholder participation and empowerment. Consumer/survivors actively participated in mental health planning and policy making, organization development, and implementation of services and supports." "Shifting the Paradigm in Community Mental Health is a guide for future research, and for consumers and administrators in the mental health field as well as in other areas of human services."--Jacket